Subcarrier allocation in multi-cell OFDMA wireless networks with non-coherent base station cooperation and controllable fairness - Han, Shiying (2013)
In this paper, a non-coherent base station cooperation (NC-BSC) scheme is examined for the downlink OFDMA wireless cellular networks. We formulate the resource allocation in the scheme as a subcarrier allocation optimization problem with equal power allocated on each subcarrier. To balance the tradeoff between system throughput and fairness, a multi-cell scenario controllable fairness is extended from single-cell scenario mentioned in [1], based on which the controllable global fairness (GF) scheme in the NC-BSC system is proposed. Two heuristic iterative algorithms are proposed to realize the subcarrier allocation in the NC-BSC system with and without the controllable fairness in a distributed manner. The performance is compared with traditional dynamic subcarrier allocation in noncooperative multi-cell networks. Simulation results show the performance enhancement through implementation of NC-BSC and the effectiveness of multi-cell controllable fairness in the NC-BSC system.